Regularised crack behaviour effects on continuum modelling of quasi-brittle materials under cyclic loading. (November 2015) - Vassaux, M.; Richard, B.; Ragueneau, F.; Millard, A.
Highlights: A full modelling approach to describe concrete behaviour under cyclic loading is presented. The identification of the parameters is carried out by virtual testing. A new constitutive model including both crack closure and hysteretic effects is proposed. The proposed approach is applied to a RC shear wall under reverse loading. Abstract: A continuum model for quasi-brittle materials able to reproduce mechanical phenomena related to cyclic loading is proposed. Specific care is taken to reproduce progressive stiffness recovery and hysteresis effects caused respectively by crack closure and friction. A virtual testing approach is set up to analyse the evolution of microscopic quantities during uni-axial cyclic tests and to justify an original and efficient modelling of these phenomena. Thus, a regularised formulation of the homogenised multiple contact problem induced by the non-simultaneous closure of microscopic cracks is presented. The proposed continuum model is validated by means of member-scale simulations of reversely loaded reinforced concrete shear walls.